Error on Elliptical Constructions made by the First Semester to the English Study Program PGRI University of Palembang - Evi Rosmiyati (Universitas PGRI Palembang, 2018)
AbstractThe main problems of this study were “What kinds and causes of error are made by the First semester to the English Study Program PGRI university of Palembang in using elliptical construction? Therefore, the purpose of this study were to find out what kindsof error and the causes are made by eleventh grade students in using elliptical constructions of First semester to the English Study Program PGRI university of Palembang. The total population of this study was 70 students consist of two classes. Choosing the sample for this study, the writer used purposive sampling method with the total 32 students. The method used in this study was the descriptive method.Written and questionnaire had been used for analyzing the data obtained. Based on the study, it is found that the error made by the eleventh grade students was 376. There were 82 (22%) errors in using ‘do’, 66 (18%) in using ‘does’, 58 (15%) in using ‘did’, 39 (10%) in using ‘am’, 78 (21%) in using ‘is’, and 53 (14%) in using ‘are’. In Addition, there were 41 errors of addition errors, 70 errors of omission errors, 211 errors of misformation errors, 46 errors of misordering errors.Keywords: Error Analysis, Elliptical construction.